Analysis of crisis in the Catholic Church: The institutional speech in the crisis of sexual abuse of minors - Cancelo-Sanmartín, Mercedes; Luna-Roldán, José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Social networks are the fruit of human interaction, but, in turn, give new shape to the dynamics of communication that creates relationships; therefore, a new attentive understanding of this environment is the prerequisite for a meaningful presence within it. In this strategic communication context of the institution, it is important to know the official discourse of the Catholic Church through the institutional digital media in the crisis of sexual abuse that it has faced in recent years.